Pergeseran Generasi dan Tensi Linguistik: Penggunaan Bahasa Gaul yang Kontroversial dalam Komunitas Pondok Pesantren Heterogen - Rahayu, Cintia Budi; Manshur, Ali (STKIP Singkawang, 2025)
This research analyzes Generational Shifts and Linguistic Tensions: Controversial Use of Slang in Heterogeneous Islamic Boarding School Communities. The aim of this research is to explore the dynamics of the use of slang among students in heterogeneous Islamic boarding schools, with a focus on how this language shapes their daily communication, analyzing the sociolinguistic impact of slang on traditional linguistic norms in the Islamic boarding school environment. The method used in this research is a qualitative method that directly observes the phenomenon of language shift in Islamic boarding schools. Based on the research results, it was found that there was a shift in language which showed a shift in the vocabulary commonly used in everyday conversation, the use of this vocabulary reflects a style of speech that is considered relaxed in interactions between peers, for example the words